2018
DOI: 10.3311/ppme.12234
|View full text |Cite
|
Sign up to set email alerts
|

Development and Comparison of Quantitative Phase Analysis for Duplex Stainless Steel Weld

Abstract: In duplex stainless steels the ideally 1:1 ratio of austenite-to-ferrite phases ensures the outstanding mechanical and corrosion properties compared to other, conventional stainless steel grades. However, this phase balance can be easily shifted to a mostly austenitic or mostly ferritic microstructures, depending on the welding process and heat input. In order to determine the phase ratio, several methods are available to use, such as Feritscope measurements, ASTM E562 manual point count method (on metallograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…[16], Varbai et al [17], and Putz et al [22], where all suggested etching followed by IA can be used to accurately measure the ferrite fraction. A suitable etching practice will minimize the required post-processing of the micrographs, otherwise a more advanced software with adjustable settings is needed to measure the ferrite fraction.…”
Section: Final Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16], Varbai et al [17], and Putz et al [22], where all suggested etching followed by IA can be used to accurately measure the ferrite fraction. A suitable etching practice will minimize the required post-processing of the micrographs, otherwise a more advanced software with adjustable settings is needed to measure the ferrite fraction.…”
Section: Final Commentsmentioning
confidence: 99%
“…In the direct approaches, the ferrite fraction is measured using optical microscopy-based techniques such as point counting (PC) and image analysis (IA) [15][16][17] and scanning electron microscopy-based techniques such as electronbackscattered diffraction (EBSD). PC is a time-consuming technique but is manual and applicable without an image analyzing program.…”
Section: Introductionmentioning
confidence: 99%
“…The application of image analysis has recently been popular with researchers for DSS characterization [38,39]. A brief description of our self-developed method [40] follows. The cut weld cross-sections were prepared for standard metallography: mounted, ground to 4000 grit paper, and polished to 3 µm diamond suspension.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…Next, the samples were color etched, using Berahas II etchant (85 mL H 2 O + 15 mL HCl + 1 g K 2 S 2 O 5 ). A 2 × 12 s etching cycle (total of 24 s etching time) was used, which was found to be optimal in our previous work [40]. The samples were rinsed in ethanol in between the two, 12 s, etching cycles.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…Advanced high-strength steels are extensively used in automotive sectors due to their extraordinary combined properties of strength, ductility, formability, high-strength to weight ratio and low CO 2 emissions [1][2][3][4][5]. Dual phase (DP) steels are a group of low-carbon micro-alloyed steels, and the term 'dual phase' indicates that the steel has two distinct phases, i.e.…”
Section: Introductionmentioning
confidence: 99%